Depressive Symptoms and Quality of Life in a Sample of Italian Women with a Diagnosis of Fibromyalgia: The Role of Attachment Styles. (16th February 2021) - Sechi, Cristina; Lucarelli, Loredana; Vismara, Laura
Abstract : Background . Women with fibromyalgia (FM) commonly suffer from depression, pervasive fatigue, and pain. The attachment style has been hypothesized to be an important factor for understanding the experience of these symptoms. Therefore, the present cross-sectional study is aimed at investigating the effect of attachment styles in women with a diagnosis of FM on depressive symptoms and quality of life. Method . Participants were 453 Italian women with a physician's diagnosis of FM with a mean age of 47 years (SD = 10.9 ). To assess attachment styles, quality of life, and depressive symptoms, women responded, respectively, to the Relationship Questionnaire, the World Health Organization Quality of Life Questionnaire, and the Beck Depression Inventory II. Results . Our results showed that the incidence of depressive symptoms was elevated, with 59% of women reporting moderate to severe symptoms. Also, the statistical analyses showed that both preoccupied and avoidant/dismissing attachments were related with depression symptoms and low perception of QoL. Conclusions . Our study demonstrates that, when evaluating the impact of FM on the QoL of women, it is important to consider the complexity of the variables that are at play. Insecure attachment styles and depressive symptoms seem to increase the likelihood of the psycho-social-somatic malaise in FM women.